An Exploration of the Information Processing Mode of Chinese Wushu’s Intrapersonal Communication - Guicun Guo; Kun Wu; Huilan Yang (Proceedings, 2022)
Based on the research methods of literature, text analysis and the theories of philosophy, communication and sports, this paper rationally discusses the information processing process of Chinese Wushu’s intrapersonal communication. It is believed that the individual body of the wushu practitioner has the general characteristics of the general information dissemination system and can actively reflect the wushu dissemination information provided by the external world. The intrapersonal communication of Chinese wushu is influenced by the distinct characteristics of individual wushu practitioners’ sociality and interactivity, which forces the individual wushu practitioners to reconstruct the significance of their own social practice of wushu communication and aggregate it into a new impetus to promote the healthy inheritance and development of Chinese wushu. In the age of digital media, the cognitive schema in the individual brain of wushu practitioners is exposed to the relevant dissemination information of wushu, which can show strong cognitive needs and have the ability to carry out in-depth cognition.